Customer-Centricity for Financial Inclusion - Kilara, Tanaya; Rhyne, Elisabeth (World Bank, Washington, DC, 2014)
Every business depends on winning customer loyalty by providing value. This is also true when customers are from the base of the social and economic pyramid (BOP). Financial service providers who are serving or who want to serve this important customer segment need to invest in understanding the customers' needs and develop products that meet those needs. An important part of becoming customer-centric is shifting profitability analysis from transactions or products to customers and even customer segments. A shift toward measuring total customer profitability involves valuing the activity of a customer over a longer time. Data analytics can help organizations make this shift in business and performance monitoring models.